Evaluation Outcome of Cone Beam Computed Tomography for Treatment Plan Success and Failure: A Systematic Review - Monica Aponte Mendez; Gözde Kayasöken; Bahareh Afjeh Soleymani; Benjamin Ravanbakhsh (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2020)
Background and aim: It is worth noting that cone beam computed tomography (CBCT) can differentiate between success and failure of treatment plans. Therefore, the main objective of this systematic review was to fulfil an outcome evaluation of CBCT for treatment plan success and failure. Materials and methods: For this purpose, the databases of Embase, PubMed, Cochrane Library, MEDLINE, Google Scholar, and the Institute for Scientific Information (ISI) were searched to perform a systematic review of the related literature on the subject matter published up to May 2020. To manage the study titles electronically, the EndNote x8 software was further utilized. Employing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), this systematic review was accordingly completed. Two reviewers then assessed the quality of the selected studies using the Methodological Index for Non-Randomized Studies (MINORS) tool. Results: A total number of 354 relevant titles and abstracts were retrieved during the electronic searches into the subject-matter literature. Ultimately, six studies were in line with the inclusion criteria in this systematic review. As well, the sample size in all studies was found to be 388 cases, and CBCT had been exercised in each one. Moreover, the follow-up timing of CBCT scans was not the same in the selected studies. Conclusion: CBCT can be useful in successful treatment, CBCT systems have highly efficient for reconstructing the 3D image of the cortical bone with a thickness of more than 1 mm vs less than 0.5 mm thickness.